Observations on the Pathology of Hydrocephalus - Dorothy S. Russell (1949)
This well illustrated, brief monograph is, according to this reviewer, the best treatment to date of the subject of hydrocephalus, with excellent discussions of the pathogenesis of this condition. The author points out that hydrocephalus is always due to a single cause, that of obstruction. Such obstruction may be caused by a congenitally malformed aqueduct, by atresia following inflammatory conditions, by periaqueductal gliosis, by variations in the Arnold-Chiari malformation or by tumors. The author feels that the term "idiopathic" is not justified in hydrocephalus. Of course, obstruction in the absorptive mechanism, the subarachnoid villi, may be one of the causes of hydrocephalus. It is truly a form of obstruction.